Enantioselective Inhibition of Human Papillomavirus L1 Pentamer Formation by Chiral-Proline Modified Calix[4]arenes: Targeting the Protein Interface - Fu, D.; Lu, T.; Liu, Y.; Wang, Y.; Li, F.; Wu, Y.; Ogden, Mark; Mocerino, Mauro (2016)
Although current human papillomavirus (HPV) vaccines can protect well against infection, they are effective only for a limited number of subtypes. Coupled with the dilemma that no efficient prescription is currently clinically available for therapy, there is an urgent need to develop new anti-HPV agents. In the present study l- and d-Proline modified calix[4]arenes (Pro- C4 A) were investigated to determine any differences in their effect on the assembly of HPV 16 L1 pentamer (L1-p). The mechanism of action using model peptides was investigated by Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS) and Nuclear Magnetic Resonance (NMR) and revealed that the binding was targeting the basic residues at L1 interface. This was also well supported by the trypsin digestion experiments and molecular simulations performed on the full-le ngth L1. The large energy and morphology differences revealed by molecular simulations explain the binding disparity of l- and d-Pro-C4 A to L1, and consequently the selective inhibition of them on L1-p forma- tion. The present study opens a way to develop enantioselec- tive and cost-effective inhibitors for L1-p formation, which might be used as a new kind of anti-HPV agent and could be extended to other viruses based on similar mechanisms.